Drivers of Quality Management in Selected Pharmaceutical Companies in Tamil Nadu : A Chi-Square Approach to Validation - Swaminathan, T. N.; Balsubramanian, G. (Prabandhan: Indian Journal of Management, 2015)
A quality management system is a system used to manage and evolve a globally competitive business, irrespective of the size of the business. A quality system is critical in the pharmaceutical industry since the products directly impinge on the well-being of the consumer. In this backdrop, the present study has examined the factors influencing the quality system management in selected pharmaceutical firms in Tamil Nadu, and also examines the relationship between selected factors and the level of the quality management system. Primary data collected in this study was analyzed using chi-square test that represents a useful method of comparing experimentally obtained data with those expected theoretically. The study concluded that of the ten variables tested, five variables namely, capital investment, percentage investment on quality control, percentage operating expenditure on quality control/assurance, ISO certification, and vendor evaluation influenced the level of the quality system in case of small firms producing pharmaceutical products, and in the case of medium and large firms, only three variables namely, percentage operating expenditure on quality control/assurance, personnel cost, and vendor evaluation influenced the level of the quality system in the study area. Percentage operating expenditure on quality control/assurance and vendor evaluation impacted and influenced the level of the quality system, irrespective of the size of the firm, that is, small, medium, or large firms in the study area.